Outcomes of Childhood Noninfant Acute Lymphoblastic Leukemia With 11q23/KMT2A Rearrangements in a Modern Therapy Era: A Retrospective International Study - Attarbaschi, Andishe; Möricke, Anja; Harrison, Christine J; Mann, Georg; Baruchel, André; De Moerloose, Barbara; Conter, Valentino; Devidas, Meenakshi; Elitzur, Sarah; Escherich, Gabriele; Hunger, Stephen P; Horibe, Keizo; et al. (Journal of clinical oncology, 2023)
PURPOSE: We aimed to study prognostic factors and efficacy of allogeneic hematopoietic stem-cell transplantation (allo-HSCT) in first remission of patients with noninfant childhood acute lymphoblastic leukemia (ALL) with 11q23/KMT2A rearrangements treated with chemotherapy regimens between 1995 and 2010. PATIENTS AND METHODS: Data were retrospectively retrieved from 629 patients with 11q23/KMT2A-rearranged ALL from 17 members of the Ponte-di-Legno Childhood ALL Working Group. Clinical and biologic characteristics, early response assessed by minimal residual disease at the end of induction (EOI) therapy, and allo-HSCT were analyzed for their impact on outcomes. RESULTS: A specific 11q23/KMT2A translocation partner gene was identified in 84.3% of patients, with the most frequent translocations being t(4;11)(q21;q23) (n = 273; 51.5%), t(11;19)(q23;p13.3) (n = 106; 20.0%), t(9;11)(p21_22;q23) (n = 76; 14.3%), t(6;11)(q27;q23) (n = 20; 3.8%), and t(10;11)(p12;q23) (n = 14; 2.6%); 41 patients (7.7%) had less frequently identified translocation partner genes. Patient characteristics and early response varied among subgroups, indicating large biologic heterogeneity and diversity in therapy sensitivity among 11q23/KMT2A-rearranged ALL. The EOI remission rate was 93.2%, and the 5-year event-free survival (EFS) for the entire cohort was 69.1% ± 1.9%, with a range from 41.7% ± 17.3% for patients with t(9;11)-positive T-ALL (n = 9) and 64.8% ± 3.0% for patients with t(4;11)-positive B-ALL (n = 266) to 91.2% ± 4.9% for patients with t(11;19)-positive T-ALL (n = 34). Low EOI minimal residual disease was associated with favorable EFS, and induction failure was particularly predictive of nonresponse to further therapy and relapse and poor EFS. In addition, EFS was not improved by allo-HSCT compared with chemotherapy only in patients with both t(4;11)-positive B-ALL (n = 64 v 51; P = .10) and 11q23/KMT2A-rearranged T-ALL (n = 16 v 10; P = .69). CONCLUSION: Compared with historical data, prognosis of patients with noninfant 11q23/KMT2A-rearranged ALL has improved, but allo-HSCT failed to affect outcome. Targeted therapies are needed to reduce relapse and treatment-related mortality rates.
Keywords: Neoplasm, Residual; biologické přípravky; Recurrence; akutní lymfatická leukemie; Biological Products; lidé; Hematopoietic Stem Cell Transplantation; Translocation, Genetic; transplantace hematopoetických kmenových buněk; recidiva; reziduální nádor; prognóza; retrospektivní studie; lymfoblastická leukemie-lymfom z prekurzorových T-buněk; Prognosis; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Chromosomes, Human, Pair 11; Precursor T-Cell Lymphoblastic Leukemia-Lymphoma; lidské chromozomy, pár 11; translokace genetická; Retrospective Studies; Humans